The Effectiveness of the Douyin Video 抖音 "桂林山水甲天下" [Guìlín Shānshuǐ Jiǎ Tiānxià] in the Chinese Comprehensive 4 Course of the Mandarin Language Education Program - Aiga Ventivani; Nadine Aliyya Qurrata A’yuni; Desti Nur Aini (Mimbar Ilmu, 2026)
This study was motivated by the low level of students’ listening and speaking skills in Mandarin language learning, which had not yet reached a level comparable to their reading and writing skills. This study aimed to examine the effectiveness of using the Douyin video “桂林山水甲天下” in the Chinese Comprehensive 4 course to improve students’ listening and speaking skills, as well as to analyze changes in students’ abilities after the treatment was administered. This study employed a quantitative approach using a one-group pretest-posttest experimental design. The participants consisted of 17 students enrolled in the Chinese Comprehensive 4 course. Data were collected through listening and speaking skill tests administered before and after the treatment using language performance test instruments. The data were analyzed using normality tests and a paired sample t-test with the assistance of SPSS 30 for Windows. The results showed that the use of Douyin videos had a significant effect on improving students’ listening and speaking skills, with a significance value of 0.001 (p < 0.05). The average listening skill score increased by 6.27 points, while the speaking skill score increased by 7.36 points after the treatment. These findings indicate that integrating short-form video-based social media can serve as an innovative alternative for improving students’ Mandarin language skills.